118=-5(-4-4p)-6p

Simple and best practice solution for 118=-5(-4-4p)-6p equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 118=-5(-4-4p)-6p equation:


Simplifying
118 = -5(-4 + -4p) + -6p
118 = (-4 * -5 + -4p * -5) + -6p
118 = (20 + 20p) + -6p

Combine like terms: 20p + -6p = 14p
118 = 20 + 14p

Solving
118 = 20 + 14p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-14p' to each side of the equation.
118 + -14p = 20 + 14p + -14p

Combine like terms: 14p + -14p = 0
118 + -14p = 20 + 0
118 + -14p = 20

Add '-118' to each side of the equation.
118 + -118 + -14p = 20 + -118

Combine like terms: 118 + -118 = 0
0 + -14p = 20 + -118
-14p = 20 + -118

Combine like terms: 20 + -118 = -98
-14p = -98

Divide each side by '-14'.
p = 7

Simplifying
p = 7

See similar equations:

| -4+15=x | | 7c-2c=42 | | x-6-17=-13 | | -7z+4+16-8z= | | X^3-6x+10x-8=0 | | 15=12k-9 | | a+(a+10)=16 | | -4c+9(3c+5)= | | 10p+18=-12 | | 13q+48=-3q | | -12(-5c-6)= | | 6+5(-3a+8)=136 | | -2=1n+2 | | 2x^4+2x^3+x^2=656 | | x-2(6.5+3.5x)=11 | | -9(5+2f)= | | -5x-7x+3+6= | | 2x-39=21 | | 8t+1=-7 | | 3(-12)-6=42 | | 50=x+y*2x | | 9-4z=1 | | -3x+8=56+5x | | -19=19+19b | | X+124+x+74=180 | | 1.25-7=53.1 | | 3(16)-6=42 | | 4x+34+90=3x | | x-3+10+x-10+2+8= | | 6+2d=18 | | -5(8+4d)-9d= | | 168=-8(4m+7) |

Equations solver categories